PENERAPAN STRATEGI BELAJAR PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 4 PADANG - Nanda, Prima; Armen, Armen; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACT Low learning outcomes at biology of students are caused by many factors , such as lack of student motivation to read and understand the material in learning biology , students tend to be passive in learning and teaching is dominated by the lead teacher resulting student learning outcomes is still below the minimum completeness  criteria  defined  by  school.  One  solution  that  can  be  done  to overcome these problems is to use learning strategies preview, question, read, reflect, Recite, review ( PQ4R ). This study aims to look at the application of learning strategies PQ4R on learning outcomes at biology of class X student of SMAN 4 Padang school year 2012/2013.This study was conducted in April-May. Experiment with this type of research study design randomized Only Control Group Design. The study population was all class X SMAN 4 Padang. Sampling was done by purposive sampling, whereas the control determination of class  and class control done by lottery, so we get the X4 as class experiment with the number of students 32 and X1 as an experimental class control by the number of students  32.  The  instrument  used  in  this  study  is  a  test  of  student  learning outcome. Based on the analysis results obtained by the average test results of the experimental  study  on  class  is  78.68  and  standard  deviation  9.63,  while  the average achievement test control class   74.46 and standard deviation 7.17. The data obtained were analyzed using t-test. Based on the analysis of data in the form of hypothesis testing performed, obtained t = 2 t-table = 1.645. Therefore t > t- table, then the hypothesis is accepted, it means that the learning outcomes of students in learning biology is becoming more increases. Application of learning strategies PQ4R has positive effects on learning outcomes at biology of class X student SMAN 4 Padang school year 2012/2013.